2011
DOI: 10.1002/jssc.201100520
|View full text |Cite
|
Sign up to set email alerts
|

Using dispersive liquid–liquid microextraction and liquid chromatography for determination of guaifenesin enantiomers in human urine

Abstract: A simple, rapid, and efficient method, dispersive liquid-liquid microextraction (DLLME) coupled with high-performance liquid chromatography-fluorescence detector, has been developed for the determination of guaifenesin (GUA) enantiomers in human urine samples after an oral dose administration of its syrup formulation. Urine samples were collected during the time intervals 0-2, 2-4, and 4-6 h and concentration and ratio of two enantiomers was determined. The ratio of R-(-) to S-(+) enantiomer concentrations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…In previous studies the separation of GUA enantiomers using polysaccharide columns was investigated. It was found that the enantiomers of GUA could be separated by normal phase HPLC using Chiralcel OD or Nucleocel Delta S columns (a tris(3,5dimethylphenyl‐carbamate) derivative of cellulose) with hexane/ethanol mobile phases. Thus, to avoid time‐consuming trial‐and‐error approaches, Lux cellulose‐1 column was first investigated because it has a similar chemical structure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous studies the separation of GUA enantiomers using polysaccharide columns was investigated. It was found that the enantiomers of GUA could be separated by normal phase HPLC using Chiralcel OD or Nucleocel Delta S columns (a tris(3,5dimethylphenyl‐carbamate) derivative of cellulose) with hexane/ethanol mobile phases. Thus, to avoid time‐consuming trial‐and‐error approaches, Lux cellulose‐1 column was first investigated because it has a similar chemical structure.…”
Section: Resultsmentioning
confidence: 99%
“…) has expectorant properties and is widely used in cough‐remedy formulations. It is used for short‐term relief of dry nonproductive cough and mucus in the breathing passages . GUA is thought to act as an expectorant by increasing the volume and reducing the viscosity of secretions in the trachea and bronchi.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1), is a constituent of guaiac resin from the wood of Guajacum officinale [1]. It is a widely used expectorant drug, and usually is taken orally to assist the bringing up of phlegm from the airway in acute respiratory tract infections and can be used for treatment sinusitis, pharyngitis, and bronchitis [2][3][4][5][6]. It is termed an expectorant since it is believed to alleviate cough discomfort by increasing sputum volume and decreasing its viscosity (hydration hypothesis), thereby promoting effective cough.…”
Section: Introductionmentioning
confidence: 99%